Effects of rare sugar d‐allulose on heat‐induced gelation of surimi prepared from marine fish. (22nd May 2017) - Ogawa, Masahiro; Inoue, Masaki; Hayakawa, Shigeru; O'Charoen, Siwaporn; Ogawa, Makiko
Abstract: BACKGROUND: d ‐Allulose (Alu), the C3‐epimer ofd ‐fructose, is a non‐caloric sweetener (0.39 kcal g −1 ) with a suppressive effect on postprandial blood glucose elevation. The aim of this study was to investigate the effects of Alu used as a sweetener and gel improver instead of sucrose on heat‐induced gelation of surimi. RESULTS: The puncture test of a heat‐induced surimi gel showed that with 50 g kg −1 Alu the gel had 15% and 6% higher gel strength than the corresponding gel with sucrose (Suc) and with sorbitol (Sor), respectively. In addition, Alu‐gel had 26% and 25% higher water‐holding capacity (WHC) than Suc‐ and Sor‐gel. Heating of myofibrillar protein with Alu, unlike Suc and Sor, facilitated the formation of both disulfide and non‐disulfide crosslinks that might be associated with the mechanical properties and WHC of Alu‐gel. CONCLUSION: Alu improves the mechanical properties and WHC of the heat‐induced surimi gel. Furthermore, Alu is low in calories compared with Suc (4.0 kcal g −1 ) and Sor (3.0 kcal g −1 ). Thus Alu will be an alternative of Suc or Sor for developing surimi‐based products with health benefits. © 2017 Society of Chemical Industry